2002
DOI: 10.1002/ffj.1097
|View full text |Cite
|
Sign up to set email alerts
|

The influence of water stress on plant height, herbal and essential oil yield and composition in Satureja hortensis L.

Abstract: The influence of soil water stress on plant height, fresh and dry weight and essential oil content of Iranian Satureja hortensis L. was investigated. The volatile constituents of the aerial parts of cultivated S. hortensis were isolated by steam distillation and analysed by GC-MS. The results showed that greater soil water stress decreased plant height and total fresh and dry weight. The accumulation of oil increased significantly under severe water stress at the flowering stage, when the mean leaf water poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
60
1
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(82 citation statements)
references
References 5 publications
16
60
1
5
Order By: Relevance
“…Our result is in agreement with the literature reports on the essential oils of Satureja hortensis and other Satureja species (Tumen et al 1998;Akgul et al 1999;Chalchat et al 1999;Sefidkon & Jamzad 2000;Kurkcuoglu et al 2001;Ghannadi 2002;Konakchiev & Tsankova 2002;Sajjadi & Baluchi 2002;Baher et al 2002;Baser et al 2004).…”
Section: Resultssupporting
confidence: 93%
“…Our result is in agreement with the literature reports on the essential oils of Satureja hortensis and other Satureja species (Tumen et al 1998;Akgul et al 1999;Chalchat et al 1999;Sefidkon & Jamzad 2000;Kurkcuoglu et al 2001;Ghannadi 2002;Konakchiev & Tsankova 2002;Sajjadi & Baluchi 2002;Baher et al 2002;Baser et al 2004).…”
Section: Resultssupporting
confidence: 93%
“…Enhanced essential oil content as a result of drought conditions was previously documented for some medicinal plants such as parsley [Petroselinum crispum (Mill.)] (Petropoulos et al, 2008) and Satureja hortensis L. (Baher et al, 2002).…”
Section: Essential Oil Contentmentioning
confidence: 99%
“…The studies on different plant species such as O. vulgare [20] and S. hortensis [21] revealed that the essential oil content tended to increase under H 2 O stress conditions. Vokou et al [22] studied the essential oils of O. vulgare ssp.…”
mentioning
confidence: 99%